Response of Traditional Boat to Ocean Waves in Operational Conditions - Satoto, Sapto Wiratno; Widiastuti, Hanifah (International Journal of Marine Engineering Innovation and Research, 2025)
Traditional boats haves played a significant role in maritime activities such as fishing, transportation, and trade, particularly in Kepulauan Riau. These boats are typically constructed from wood, with hull designs passed down through generations. However, this traditional approach raises potential safety concerns due to the absence of standardized construction practices and compliance with maritime safety regulations. Reports of frequent accidents suggest that human factors and inadequate hull responses to wave conditions are contributing causes. This study aims to analyze the response of traditional boats from Riau Islands using numerical simulation methods. The analysis is conducted using Maxsurf software, particularly Maxsurf Motions and Maxsurf Stability, applying the linear wave theory approach to evaluate pitch, roll, and heave responses under variations in loading, speed, and wave direction. The results indicate that the boat’s intact stability and seakeeping performance meet IMO safety criteria (C1–C6) under both stationary and 6-knot speed conditions. The seakeeping evaluation conducted using Olson’s criteria under wave height variations ranging from 0.5 to 1.0 meters demonstrates that the vessel’s response consistently remains below the maximum permissible threshold. This research provides initial data and insights to better understand the intact stability and seakeeping characteristics of traditional boats in Riau Islands, particularly regarding their wave response behavior.